PENGARUH PENGGUNAAN APLIKASI CHATGPT TERHADAP MINAT BELAJAR MURID PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) KELAS X DI SMAN 24 KABUPATEN TANGERANG - Putri Khoirunnissa Azahra; Nur Halimah; Hasim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Chatgpt application is an Artificial Intelligence (AI)-based technology utilized as an interactive learning medium. In the learning process, it can assist students in obtaining information quickly, understanding learning materials more easily, increasing engagement in learning activities, and is expected to enhance students' learning interest. The objectives of this study are: (1) to determine the influence of Chatgpt application usage on students' learning interest in the Islamic Religious Education (PAI) subject for Grade X students at SMA Negeri 24 Tangerang Regency, and (2) to determine the extent of the influence of Chatgpt application usage on students' learning interest in the Islamic Religious Education (PAI) subject for Grade X students at SMA Negeri 24 Tangerang Regency. This study employed a quantitative research method with a simple linear regression approach. Data were collected through questionnaire surveys and analyzed using SPSS version 27. The sampling technique used was random sampling involving 206 students. The results showed that the R Square value was 0.953 or 95.3%, with a significance value of 0.000 < 0.05. Based on the t-test, the calculated t-value was 64.215, which was greater than the t-table value of 1.971. Therefore, it can be concluded that the use of the Chatgpt application has a significant influence on students' learning interest in the Islamic Religious Education (PAI) subject for Grade X students at SMA Negeri 24 Tangerang Regency, accounting for 95.3% of the variance, while the remaining 4.7% is influenced by other factors not examined in this study.